Customer lifetime value as a predictor for future prospect of retailer's survival: A review of customer lifetime value model - Bohari, Abdul Manaf; Rainis, Ruslan; Marimuthu, Malliga (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Customer lifetime value is the top priority issues in every segment of business and it’s become more significance during the world wide economy crisis. Estimating customer lifetime value of retailer’s business plays important roles in determine the most profitable customer’s to the business, as well as sustaining the performance of business, both short and long run operation. In perspective of global meltdown economy, specifically, the use of customer lifetime value will became as central issues because it has major influence on the strategy that adopted by the business. As a predictor of future prospect of retailer’s survival, customer lifetime value are developed based on financial items/method, as well as payback period, net present value, return on investment, return on equity, and so on. Thus, the objective of the paper is to review’s the model of customer lifetime value in-prospecting the future prospect of retailer’s survival in the marketplace. For that, advantages and disadvantages of models are discussed. In addition, to the best of knowledge, there are limited discussions on the reasons of adopting the customer lifetime approach for prospecting the lifetime value of retailer’s business, includes hypermarket business. Thus, discussion on the reasons of adopting the model was made with specific reference to hypermarket business. Moreover, it is important to the manager to understand the capabilities and constrains of those methods because it can affect the financial strategy of the business. At the end, suggestion was made on how to improvise the performance of estimates the customer lifetime value, accordingly to the chance of customer value in the geographical marketplace.